Management Behavior: A Qualitative Exploration - Asty, Herfyna (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This research that student who are accustomed to using time management techniques such as setting goals, using to-do lists, and setting specific times for each activity, can achieve their academic goals more efficiently. The ability to organize and prioritize time effectively allows them to maximize their learning potential and achieve better academic results. Researcher interested in conducting to identify how students apply time management behavior to maximize their personal learning for English students at the University PGRI Sumatera Barat. In this research used qualitative data to obtain data. Researcher have received 3 students from class A and 3 students from class B as a sample, researcher have done audio recording from interview.